2021
DOI: 10.1101/2021.12.15.472743
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nest aggregations of wild bees and apoid wasps in urban pavements: a “street life” to be promoted in urban planning

Abstract: In the last 10 years, knowledges of wild bees and apoid wasps’ community dynamics have gained interest in urban ecology focusing on the availability of floral resources in cities. Although understudied, the urban environment impacts the conditions of their nesting sites. Recent observations in the Brussels-Capital Region (Belgium) showed that urban pavements can be a novel nesting opportunity for Hymenoptera ground-nesting species such as wild bees and apoid wasps. Here, using citizen science, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 63 publications
0
2
0
1
Order By: Relevance
“…This sampling method allows for a larger geographical scope due to the time saved at each site and will give a better chance to find rare species. The locations from the dataset of Noël et al (2021) were used as a basis for the search for nests in order to cover as much territory as possible with a high probability of observing ants. An anthill was located on a pavement, either thanks to the sand mound between two paving stones or thanks to an ant followed to its anthill (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This sampling method allows for a larger geographical scope due to the time saved at each site and will give a better chance to find rare species. The locations from the dataset of Noël et al (2021) were used as a basis for the search for nests in order to cover as much territory as possible with a high probability of observing ants. An anthill was located on a pavement, either thanks to the sand mound between two paving stones or thanks to an ant followed to its anthill (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies focusing on the insect biodiversity of urban areas revealed the presence of several Hymenoptera species which can nest under urban pavements. These studies focused mainly on the nesting ecology of solitary bees and digger wasps, but also recorded some ant species ( Noël et al 2021 , Weber 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lessons from metapopulation ecology and a better understanding of patch quality for specific taxa will be critical to raising urban insect diversity and conserving this as a stable ecosystem component (e.g., Azhar et al, 2024; Liao & Lin, 2024). There are pathways to understanding patch improvement, but above this, integrating connectivity and opportunity for insects in urban areas more broadly and by design will contribute further (e.g., Noël et al, 2024) as will translocations to restore extirpated diversity (e.g., Yagui et al, 2024).…”
Section: In Summarymentioning
confidence: 99%
“…The ability of some invertebrates to adapt to these is documented, including green roofs (Wang et al, 2022), golf courses and lawns (Colding & Folke, 2009) and abandoned or waste lands (McKinney, 2021). Successful insect use of these habitats, such as ornamental garden ponds (Hill et al, 2024) or urban pavements (Noël et al, 2024), may be influenced by context‐specific environmental, management and social factors. Some studied habitats can be locally specific to countries, regions or urban typologies and may be inherently tied to local social and political history.…”
Section: Priorities For Urban Insect Ecology Research and Conservationmentioning
confidence: 99%
“…De plus, une forte concentration de nids a Entomologie Faunistique -Faunistic Entomology 2022-75 pu être mise en évidence dans la rue Achille Reisdorff du quartier Myosotis (Figure 4 et 5). Cette espèce a également la particularité de nicher à travers le joint de certains vieux trottoirs bruxellois (Noël et al, 2021). Cette bourgade était composée en majorité de nids de D. hirtipes, mais également de nids d'Halictus scabiosae, même si pour cette dernière, nous avons des occurrences dans le nouveau quartier Engeland.…”
Section: Mise En Place De La Collection Entomologiqueunclassified